Edukasi Web Woop Self-Management pada Siswa SMA (Alternatif Menurunkan Social Media Addiction ) - Reike Kumalasari; Yennisa Nanda Prastiwi; Anit Savia Damayanti; Shinta Uqbadamayanti; Selvira Risti Pamasih; Suwanti (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
The development of social media such as TikTok and YouTube Shorts has a significant impact on the lives of teenagers, especially in psychological aspects and social behavior. Excessive use of social media can lead to addiction, reduce self-control, and impact mental health and academic achievement. This Community Service activity aims to increase student literacy about the web which is useful for reducing social media addiction. This website is about training self-management through the WOOP method (Wish, Outcome, Obstacle, Plan). The approach used in this service is an educational approach (Educational/Training Approach). The activity is carried out with a focus on increasing students' knowledge and skills in using the web. The activity was carried out at SMA Negeri 2 Ungaran involving 40 students. The results of the activity showed an increase in knowledge and skills in using the web as shown by students being able to use the web by identifying goals (wish), obstacles (obstacle), results (Outcome), concrete plans (plan) to reduce excessive use of social media. Thus, WOOP Self-Management web education has been proven to be able to increase students' knowledge and skills in using WOOP self-management web to reduce the level of social media addiction and increase healthy digital behavior in adolescents. This program is recommended to be integrated into school guidance and counseling activities to support character development and students' mental health.   ABSTRAK Perkembangan media sosial seperti TikTok dan YouTube Shorts memberikan dampak signifikan terhadap kehidupan remaja, khususnya dalam aspek psikologis dan perilaku sosial. Penggunaan media sosial yang berlebihan dapat menimbulkan kecanduan, menurunkan kontrol diri, serta berdampak pada kesehatan mental dan prestasi akademik. Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan literasi siswa tentang web yang yang berguna untuk menurunkan addiksi/ kecanduan sosial media. Web ini tentang  melatih self-management melalui metode WOOP (Wish, Outcome, Obstacle, Plan). Pendekatan yang digunakan dalam pengabdian ini dengan pendekatan edukasi (Educational/Training Approach).Kegiatan dilaksanakan fokusnya pada peningkatan pengetahuan dan keterampilan siswa dalam menggunakan web. Kegiatan dilakukan di SMA Negeri 2 Ungaran dengan melibatkan 40 siswa. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan ketrampilan dalam menggunakan web yang ditunjukkan dari siswa mampu menggunakan web dengan mengidentifikasi tujuan (wish), hambatan (obstacle), hasil (Outcome), rencana konkret (plan) untuk mengurangi penggunaan media sosial secara berlebihan. Dengan demikian, edukasi web WOOP Self-Management terbukti mampu meningkatkan pengetahuan dan ketrampilan siswa dalam menggunakan web WOOP self-management untuk menurunkan tingkat social media addiction dan meningkatkan perilaku digital yang sehat pada remaja. Program ini direkomendasikan untuk diintegrasikan ke dalam kegiatan bimbingan konseling sekolah guna mendukung pengembangan karakter dan kesehatan mental siswa.